2009
DOI: 10.2486/indhealth.47.283
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Subjective Symptoms and Cold Prevention Measures in Winter between Traffic Control Workers and Construction Workers in Japan

Abstract: To help making comfortable workplaces and to prevent health disorders induced by the exposure to moderate cold in two different groups of out-door workers, we conducted a survey to compare subjective symptoms and cold prevention measures in winter between traffic control workers and construction workers. The subjects of this study were 98 male traffic control workers and 149 male workers engaged in building construction. Work loads of traffic control workers and construction workers were estimated at RMR1~2 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 15 publications
0
9
0
Order By: Relevance
“…High temperature can cause heat rash, heat exhaustion, and heatstroke in construction workers [4]. Low temperature in winter also can cause fatigue, lumbago, and cold finger sensation [6]. Rameezdeen and Elmualim (2017) insisted that heat stress causes heat rash, heat cramp, heat fainting, heat exhaustion and heatstroke in construction workers [4], Mohammed et al (2019) noted how productivity losses, illnesses and injuries to workers may arise due to hot and humid weather conditions [13].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…High temperature can cause heat rash, heat exhaustion, and heatstroke in construction workers [4]. Low temperature in winter also can cause fatigue, lumbago, and cold finger sensation [6]. Rameezdeen and Elmualim (2017) insisted that heat stress causes heat rash, heat cramp, heat fainting, heat exhaustion and heatstroke in construction workers [4], Mohammed et al (2019) noted how productivity losses, illnesses and injuries to workers may arise due to hot and humid weather conditions [13].…”
Section: Discussionmentioning
confidence: 99%
“…These issues can be related to fatal incidents or injuries caused by physical fatigue, mental disorder, slow response speeds, and poor reasoning abilities [ 5 ]. On the other hand, cold temperatures in winter can cause fatigue, lumbago, cold finger sensation, rigidity of the body, and shoulder and neck stiffness [ 6 ]. It has been reported that work conditions under 10 °C have a negative influence on concentration, memory, and performance capacity [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Table 2. Reported backache by sector and gender (Eurofound, 2007) It is reported that the ranges of a point or annual prevalence of LBP were from 27% to 75% for farmers (Kumudini & Hasegawa, 2009;Liu et al, 2011;Milosavljevic et al, 2011;O'Sullivan et al, 2009;Taechasubamorn et al, 2011), from 44% to 74% for drivers (Alperovitch-Najenson , 2010;Bovenzi, 2009;Rozali et al, 2009), from 32% to 78% for mine workers (Bio et al, 2007;Sarikaya et al, 2007), from 20% to 23% for construction workers (Inaba et al, 2007(Inaba et al, , 2009, from 46% to 83% for care workers (Jensen et al, 2009;Minematsu, 2007;Sorensen et al, 2011;Yalcinkaya et al, 2010) in recent studies. Guo et al reported the highest risk of back pain was among construction workers (22.6%) for men and among nursing aides (18.8%) for women (Guo et al, 1995).…”
Section: Prevalence Of Occupational Lbpmentioning
confidence: 99%
“…Inaba et al 11) report a higher frequency of shoulder and neck stiffness in traffic controllers and fatigue and lumbago in construction workers. Authors conclude that preventive measures are not sufficient for these workers to avoid risks of cold related disorders.…”
mentioning
confidence: 97%